Uprima® ในการรักษาภาวะ Erectile Dysfunction - Sangdee, Chaichan (Journal of Basic and Applied Pharmacology, 2015)
Erectile dysfunction (ED) is defined as the persistent or repeated inability to attain or to maintain an erection firm or long enough for satisfactory intercourse. There are many causes that can lead to ED including organic, psychogenic or both. Recently, ED receives an intense interest since we learn more on the physiology of erection together with the availability of new and successful treatment regimens. The first drug with proven efficacy is sildenafil, however, this drug carries several disadvantages and serious interaction with nitrates. Apomorphine HCl sublingual (Uprima®) is recently introduced to treat ED with impressive results. It is the only drug that works on the central mechanism to activate the dopamine system and thus to producing erection closely resemble to naturally induced erection. Uprima® has several advantages including fast acting, its erectogenic effect lasts for 2 hours, multiple daily dosing possible, consistent effect with no tolerance on long terrn use, effective in organic, psychogenic ED or both. The drug is well tolerated with good acceptability profile. There are few side effects associated with Uprima®, they are usually mild in nature and usually disappear after chronic use.